Employee affective commitment to change, leadership styles and organisational culture: A case of Yemen public sector - Gelaidan, Hamid Mahmood; Ahmad, Hartini (2011)
The purpose of this study is to examine the effect of leadership style on affective commitment to change, moderates by the organisational culture.The research adopts both qualitative and quantitative approaches through survey with 371 employees of public organisations in Yemen, as well as interviews with the managers. The findings showed transformational leadership was positively related to the employee’s affective commitment to change; similar to the transactional leadership was positively related to the affective commitment to change. The results showed organisational culture had positively moderate the relationship between the leadership styles and employee affective commitment to change. Finally, the findings revealed the transactional leadership was a strong predictor to affective commitment to change compared with the transformational leadership.